PROTEIN REKOMBINAN 38 KDA MYCOBACTERIUM TUBERCULOSIS DALAM INTERLEUKIN-2 DAN INTERLEUKIN-4 SERTA LIMFOSIT T CD3+ (The Mycobacterium Tuberculosis 38 kDa Recombinant Protein in Interleukin-2 and Interleukin-4 as well as CD3+ T Lymphocytes) - Maimun Z Arthamin; Nunuk S Muktiati; Triwahju Astuti; Tri Yudani M Raras; Didit T Setyo Budi; Francisca S. Tanoerahardjo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Tuberculosis remains a serious global health problem despite the widespread use of the vaccine against tuberculosis (TB). Up tonow, the only available TB vaccine, Mycobacterium bovis BCG has a very wide efficacy range from 0 until 80 percent protection sothe development of a new vaccine is needed. The new protein as a candidate vaccine should be assessed for their immunogenicity. Thepurpose of this study was to examine whether Mycobacterium tuberculosis 38 kDa recombinant protein could stimulate a cellularimmune response especially CD3+T lymphocytes to express IL-2 and IL-4 in PBMC cultures. An experimental laboratory research oncultured PBMC of 3 groups consisting of TB patients, contacts of TB positive and healthy subjects, each group consisted of 8 subjects. AllPBMC cultures were induced by Mycobacterium tuberculosis 38 kDa recombinant protein, Purified Protein Derivative (PPD) and withoutantigen as a control. Expression of IL-2 and IL-4 CD3+ T lymphocytes was measured with flowcytometry. In healthy volunteers and TBcontacts there was a significant difference in the expression of IL-2 and IL-4 CD3+ T lymphocytes compared with no any treatment. Thehighest IL-2 expression was in healthy subjects [8.13 (0.622)] while the highest expression of IL-4 was in TB patients [6.436 (4.586)].Mycobacterium tuberculosis 38 kDa recombinant protein could induce the expression of IL-2 and IL-4 of CD3+ T lymphocytes in healthysubjects, TB contacts and TB patients and there were a significance differences in the expression of all groups.